The impact of whistle-blowing on the effectiveness of forensic audits and investigative audits in fraud detection: A multigroup analysis of gender and experience - Urumsah, Dekar; Rahmida, Mislya; Hamdani, Rizki; Aji, Seto Satriyo Bayu (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
The study investigates the impact of whistle-blowing, forensic audit, and investigative audit on fraud detection, with gender and experience serving as potential moderators. Structured equation modeling (SEM) is used to study the relationships between determinants. This study also seeks to understand the role of gender and experience in determining fraud detection through multigroup analysis. The data used for the analysis includes 97 auditors from the Supreme Audit Agency (BPK RI) and the Financial and Development Supervisory Agency (BPKP) who work in the investigation unit. The findings reveal that whistle-blowing positively and significantly influences forensic audit, investigative audit, and, ultimately, fraud detection. Both forensic and investigative audits also exhibit positive and significant impacts on fraud detection. Moderation effects of gender and experience were not observed in the relationships between whistle-blowing and the aforementioned audits or fraud detection. These findings suggest that the implementation of whistle-blowing systems can facilitate fraud reporting, improve early warning for fraud detection, and function as an effective oversight tool to prevent internal violations in government institutions. This study contributes valuable empirical evidence regarding the interplay between whistle-blowing, forensic and investigative audits, fraud detection, and the moderating roles of gender and experience. It effectively addresses knowledge gaps and offers potential contributions to existing theories, particularly concerning the nuanced influence of gender and experience on fraud detection.